Aspek Hukum Perdata Dalam Penyelesaian Sengketa Investasi Berkelanjutan Di Indonesia - Azis, Yuldiana Zesa; Ali Muddin, Ahmad (Jurnal Restorative Justice, 2025)
Sustainable investment plays a crucial role in Indonesia's economic development by emphasizing a balance between economic growth,environmental protection, and social welfare. Despite a significant increase in investment in strategic sectors such as energy and infrastructure, the main challenge is managing the negative impact on the environment and local communities. This article discusses the role of civil law in resolvingdisputes arising from conflicts between economic interests and environmental or social needs. Civil law, through mechanisms such as the filing of lawsuits in court, mediation, and arbitration, serves as a tool to bridge conflicting interests and ensure fair settlements. The development ofpolicies and legal instruments that support sustainability is also important to maximize the benefits of investment while maintaining a balancebetween various interests.